Validasi Kuesioner Elemen PBL yang Mempengaruhi Keputusan Belajar Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan - Galuh Suryandari; Yayi Suryo Prabandari; Rossi Sanusi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2015)
Background: Several elements of PBL have been identified and prepared with a questionnaire to be reused. Variables of PBL elements that influence students' learning decisions are assessed using a questionnaire of PBL elements that affect students’ learning decisions. This study is one part of a study reported in a different journal of medical education. The objective of this study was to validate a questionnaire of PBL elements that influence learning decisions of students in FKIK UMYMethods: A total of 584 students from major A, B, C, and D in FKIK UMY on the introductory tutorial groups with Indonesian as discussion language were invited to fill out a questionnaire. Construct validity was assessed by testing the validity of the items, Crönbach alpha, factor analysis, convergent and discriminate validity.Results: A total of 582 students of the major A, B, C, and D FKIK UMY on the tutorial groups with Indonesian as the language of instruction participated in the study (response rate 99.6%). Data showed that the questionnaire on PBL elements that affect student learning decisions have a high construct validity.Conclusion: The questionnaire of PBL elements that influence students’ learning decisions in Indonesian version is valid and can be reused. A deeper, further qualitative research on the other PBL elements can be conducted to improve the questionnaire.